2020
DOI: 10.1111/1759-7714.13620
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐429 suppresses proliferation and invasion of breast cancer via inhibiting the Wnt/β‐catenin signaling pathway

Abstract: Background microRNAs ( miRNAs) have been verified as molecular targets for regulating tumor proliferation, invasion, and metastasis in tumor progression. However, the relationship between miRNAs and cellular energy metabolism in breast cancer still needs to be clarified. This study aimed to investigate the role of miR‐429 in breast cancer progression. Methods Bioinformatic analyses were employed to detect the relationship between miR‐429 and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 29 publications
(46 reference statements)
0
12
0
Order By: Relevance
“…In our study, MUC14 was significantly downregulated in breast cancer, possessed statistical ability to distinguish breast cancer tissues from normal breast tissues and its downregulation indicated poor prognosis in breast cancer. Previous investigations also showed that MUC14 was a prognostic biomarker for several types of human cancer, including hepatocellular carcinoma [22], gastric cancer [23], diffuse type gastric cancer [24] and clear cell renal cell carcinoma [25]. To date, no research regarding expression, diagnosis and prognosis of MUC14 in breast cancer has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, MUC14 was significantly downregulated in breast cancer, possessed statistical ability to distinguish breast cancer tissues from normal breast tissues and its downregulation indicated poor prognosis in breast cancer. Previous investigations also showed that MUC14 was a prognostic biomarker for several types of human cancer, including hepatocellular carcinoma [22], gastric cancer [23], diffuse type gastric cancer [24] and clear cell renal cell carcinoma [25]. To date, no research regarding expression, diagnosis and prognosis of MUC14 in breast cancer has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-429 has a tumor-promotion role in some cancers. However, miR-429 appears to have a tumor-suppressing role in many cancers, including breast cancer [ 32 ], bladder cancer [ 33 ], and thyroid cancer [ 34 ]. The inhibition of miR-429 could suppress the proliferation, migration, and invasion of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Opposing results were observed when cells were transfected with miR-1976 mimics, and the authors attributed a reduced presence of lung metastasis in vivo to miR-1976-induced alterations in EMT and the CSC pool [60]. Similarly, miR-429 has been shown to reduce proliferation, migration, and invasion, as well as EMT, in breast cancer cells in vitro and to inhibit bone metastasis in vivo [62]. A reduced invasion capacity was also observed in the MDA-B02 bone metastatic breast cancer cell line upon overexpression of miR-30b-d, miR-30b-c, or miR-30a-b-c-d-e [63].…”
Section: Direct Effects Of Mirnas On Breast Cancer Cells and Metastasismentioning
confidence: 98%
“…Regarding breast cancer and metastatic bone disease, several in vivo studies demonstrated miRNA-mediated effects on the bone microenvironment leading to reduced tumor growth and attenuated osteolytic disease. For example, high levels of miR-30 [63], miR-124 [46], miR-192 [31], and miR-429 [62] have been shown to have a beneficial effect with reduced osteolysis in vivo. In addition to osteolytic lesions, the frequency of bone metastasis or tumor burden in general can be altered by differential miRNA expression.…”
Section: Therapeutic Implications Of Mirnas In Metastatic Bone Diseasementioning
confidence: 99%